1839 Tex. Gen. Laws 172, An Act Concerning Slaves, § 6 - (:unkn) unknown (My University, 1839)
Prohibited any "slave" from carrying firearms or weapons without the consent of his master.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES